Trade‐offs between fire hazard reduction and conservation in a Natura 2000 shrub–grassland mosaic. Issue 1 (27th November 2019) - Silva, Vasco; Catry, Filipe X.; Fernandes, Paulo M.; Rego, Francisco C.; Bugalho, Miguel N.
Abstract: Questions: What are the effects of time since prescribed burning on plant species composition and diversity in a Natura 2000 shrub–grassland mosaic? Is it possible to use prescribed burning to reduce fire hazard and simultaneously maintain conservation status in such habitat types? Location: Sintra‐Cascais Natural Park, Portugal. Methods: We assessed differences in plant species composition, plant diversity, vegetation structure and above‐ground plant biomass between plots treated with prescribed burning (two, four and six years after fire) and untreated plots in a mosaic of Natura 2000 dry shrub–grasslands, and assessed potential fire behaviour differences between treatments. Results: Plant species richness and diversity were higher two and four years after prescribed burning, in comparison with untreated plots. Cover of herbaceous species and non‐resprouters was higher, and cover of shrubs was lower, but only two years after fire. Habitat structure and phytovolume of the indicator species Ulex jussiaei was affected negatively up to six years after prescribed burning, indicating changes in conservation status from Favourable to Unfavourable. Prescribed burning reduced above‐ground biomass and fire simulations showed that potential fire hazard was also reduced, particularly in two‐year‐old plots. Conclusions: Prescribed burning increased plant diversity in the short term, reduced fuel loads and fire hazard, but negatively affected habitat conservation status. We show that there are potential trade‐offs between fire hazard mitigation and conservation in a Natura 2000 shrub–grassland habitat type and that these must be considered during fuel management decisions. Abstract : Prescribed burning increased plant diversity in the short term, reduced fuel loads and fire hazard, but negatively affected habitat conservation status. We show that there are potential trade‐offs between fire hazard mitigation and conservation in a mosaic of dry Mediterranean Natura 2000 shrub–grassland habitat types and that these must be considered during fuel management decisions.